An investigation of stable sulphur isotopes as a palaeodietary indicator in South Africa - Johnson, Malia (Department of Archaeology, 2015)
The purpose of this thesis is to assess the use of stable sulphur isotope analysis as a tool for studying the diet and mobility of Later Stone Age people in the Western Cape Province of South Africa.